(untitled) (Research, Society and Development, 2022)
This article is an integrative literature review that aims to answer the question “what are the factors involved in the experience of sexuality in people with HIV/AIDS?”. For this, LILACS and VHL research databases were used, the health descriptors (DeCS) sexuality and HIV and Aids, considering the publications in Portuguese of the last five years. The search resulted in 64 articles, which after analyzing and excluding those that did not meet the requirements, 8 articles were selected that corresponded to the objective, being read and analyzed in full. The discussion grouped ways of experiencing sexuality based on HIV/AIDS in different groups, in relation to sex and age group, and was divided into three stages: 1 – Experience of sexuality in the face of HIV by women; 2 – Experience of sexuality in the face of HIV of men who have sex with men (MSM); and finally 3 – Experience of sexuality in the face of HIV: from adolescence to old age. It was concluded that people living with HIV/Aids (PLHA) experience stigma and prejudice in their experiences due to sexuality. These produce feelings of guilt and fear in two perspectives: in relation to infecting others and abandonment and exclusion after the diagnosis is revealed.